Analisis Faktor Yang Mempengaruhi Keterlambatan Pengobatan Pada Wanita Penderita Kanker Payudara Di Rumah Sakit Umum Daerah Simeulue Tahun 2018 - Kartini Kartini; Namora Lamongga Lubis; Tengku Moriza (JURNAL INFO KESEHATAN, 2019)
Breast cancer can be detected early by conducting breast self-examination (REALIZING) which aims to prevent the advanced risk and can reduce the mortality rate in patients, because cancer can be found early so it will give Longer life expectancy. The aim of this researcher is to know the factors of late treatment in women with breast cancer in the district of Simeulue HOSPITAL in 2018. This research is a qualitative method of research that is done with the main goal to make a description or a descriptions of the delay treatment in women who suffer from breast cancer in the district HOSPITAL, Simeulue. Data analysis includes data processing with data reduction, display data, and conclusion or verificasion stages. The results of the study obtained the delay of treatment of breast cancer one of them by the level of education of the informant, knowledge and treatment facilities that are less complete, resulting in a delay in Breast cancer treatment. As a family support factor, friends and health workers only convince the informant to immediately treat the illness completely. The delay in treatment is low education and knowledge, late treatment at the previous treatment is incomplete, the delay of treatment due to the three components of this factor either family, friends or officers Health only strengthens the informant to immediately treat the disease.